Zinc water chemistry reduces dissolution of FeCrAl for nuclear fuel cladding. (15th April 2022) - Rebak, Raul B.; Jurewicz, Timothy B.; Larsen, Michael; Yin, Liang
Abstract: The use of accident tolerant fuels (ATF) will facilitate the continuing operation of light water reactors (LWR) by making them safer and more economical to operate. One of the ATF concepts is to use iron-chromium-aluminum (FeCrAl) alloys for the cladding of the fuel. These ferritic alloys were never used in power reactors before therefore their behavior needs to be characterized. Current results show a positive effect of zinc chemistry on the environmental degradation of ferritic FeCrAl. Autoclave tests at 288 °C show > 60% decrease in the dissolution rate of FeCrAl and 3–4 time decrease in the surface oxide film thickness. Highlights: This manuscript is original, showing the effect of Zn additions on the protectiveness of oxides formed on FeCrAl alloys. The effect of Zn on minimizing the degradation of FeCrAl was similar to that of other Cr containing alloys, e.g. 316 L SS & Inconel 600/690. Zinc incorporates into the upper layer of the oxide film formed on FeCrAl alloys. Zinc decreases the mass loss of FeCrAl in 288 °C water by over 60%.